Clinical and Radiographic Results of Indirect Decompression and Posterior Cervical Fusion for Single-Level Cervical Radiculopathy Using an Expandable Implant with 2-Year Follow-Up - Siemionow, Kris; Janusz, Piotr; Phillips, Frank M.; Youssef, Jim A.; Isaacs, Robert; Tyrakowski, Marcin; McCormack, Bruce (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Background Indirect posterior cervical nerve root decompression and fusion performed by placing bilateral posterior cervical cages in the facet joints from a posterior approach has been proposed as an option to treat select patients with cervical radiculopathy. The purpose of this study was to report 2-year clinical and radiologic results of this treatment method.Methods Patients who failed nonsurgical management for single-level cervical radiculopathy were recruited. Surgical treatment involved a posterior approach with decortication of the lateral mass and facet joint at the treated level followed by placement of the DTRAX Expandable Cage (Providence Medical Technology, Lafayette, California, United States) into both facet joints. Iliac crest bone autograft was mixed with demineralized bone matrix and used in all cases. The Neck Disability Index (NDI), visual analog scale (VAS) for neck and arm pain, and SF-12 v.2 questionnaire were evaluated preoperatively and 2 years postoperatively. Segmental (treated level) and overall C2–C7 cervical lordosis, disk height, adjacent segment degeneration, and fusion were assessed on computed tomography scans and radiographs acquired preoperatively and 2 years postoperatively.Results Overall, 53 of 60 enrolled patients were available at 2-year follow-up. There were 35 females and 18 males with a mean age of 53 years (range: 40–75 years). The operated level was C3–C4 (N = 3), C4–C5 (N = 6), C5–C6 (N = 36), and C6–C7 (N = 8). The mean preoperative and 2-year scores were NDI: 32.3 versus 9.1 (p < 0.0001); VAS Neck Pain: 7.4 versus 2.6 (p < 0.0001); VAS Arm Pain: 7.4 versus 2.6 (p < 0.0001); SF-12 Physical Component Summary: 34.6 versus 43.6 (p < 0.0001), and SF-12 Mental Component Summary: 40.8 versus 51.4 (p < 0.0001). No significant changes in overall or segmental lordosis were noted after surgery. Radiographic fusion rate was 98.1%. There was no device failure, implant lucency, or surgical reinterventions.Conclusions Indirect decompression and posterior cervical fusion using an expandable intervertebral cage may be an effective tissue-sparing option in select patients with single-level cervical radiculopathy.
Keywords: DTRAX Facet System; posterior cervical fusion; cervical radiculopathy; cervical spondylosis; minimally invasive surgery